Comparison of high‐power short‐duration and low‐power long‐duration radiofrequency ablation for treating atrial fibrillation: Systematic review and meta‐analysis - Chen, Chao‐feng (Wiley Periodicals, Inc., 2020)

(untitled) (Clin Cardiol)
BACKGROUND: High power shorter duration (HPSD) ablation seen to increase efficacy and safety treating of atrial fibrillation (AF); however, comparative data between HPSD and low power longer duration (LPLD) ablation are limited. HYPOTHESIS: We thought that HPSD might bring more clinical benefits. The aim of this meta‐analysis was to evaluate the clinical benefits of HPSD in patients with AF. METHODS: The Medline, PubMed, Embase, and the Cochrane Library databases were searched for studies comparing HPSD and LPLD ablation. RESULTS: Ten trials with 2467 patients were included in the analysis. Pooled analyses demonstrated that HPSD showed a benefit of first‐pass pulmonary vein isolation (PVI) (risk ratio [RR]: 1.20; 95% confidence interval [CI]: 1.10‐1.31, P < .001) and recurrence of atrial arrhythmias (RR: 0.73; 95% CI: 0.58‐0.91, P = .005). Additionally, HPSD could reduce procedural time (weighted mean difference [WMD]: −42.93; 95% CI, −58.10 to −27.75, P < .001), ablation time (WMD: −21.01; 95% CI: −24.55 to −17.47, P < .001), and fluoroscopy time (WMD: −4.11; 95% CI: −6.78 to −1.45, P < .001). Moreover, major complications and esophageal thermal injury (ETI) were similar between two groups (RR: 0.75; 95% CI: 0.44‐1.30, P = .31) and (RR: 0.57; 95% CI: 0.21‐1.51, P = .26). CONCLUSIONS: HPSD was safe and efficient for treating AF. Compared with LPLD, HPSD was associated with advantages of procedural features, higher first‐pass PVI and reducing recurrence of atrial arrhythmias. Moreover, major complications and ETI were similar between two groups.